Insights on the safety of carotenogenic Chlorella vulgaris in rodents - Sampayo, C. (2014)
Chlorella vulgaris (Cv) biomass is widely used as a traditional food in the Orient and its safety for human consumption has been proved. However, carotenogenic biomass (orange), resulting from induced stresses, needs further safety evaluation, which is the aim of this study. The preliminary toxicological characterization of Cv consisted of a single dose (mice), repeated dose studies (mice and rats) and a biodisposition evaluation (rats). Nomortalities nor relevant clinical signs or behavioural changeswere observed inmice or in rats. The carotenoids in the rat faecal matter suggest that the carotenoids contained in Cv have been absorbed through a potentially saturated transport across the intestinalwall. No safety concerns were identified based on clinical signs, biochemical parameters, and liver and spleen histopathology. No significant differences in food/water intake, blood-pressure, blood glucose levels, glucose tolerance and plasticity of erythrocytes were observed over one month with both supplemented and control animals. The intake of carotenogenic Cv did not reveal any signs of toxicity for doses far exceeding the proposed carotenoid human-diet dose. Therefore these preliminary results suggest that the orange Cv microalgae can be used as a source of carotenoids and could be used for human consumption with possible health benefits.